Countertransference: A phenomenon that enriches the therapeutic process: A literature review with clinical illustrations - Cox, Rachel L. (Auckland University of Technology, 2005)
The objective of this literature review was to understand and describe the complex theoretical concept of countertransference and to identify how countertransference helped the therapist to understand the client’s psychological processes. Literature on countertransference from the past century has been examined using a modified systematic literature review, and psychodynamic concepts that underpin countertransference have been identified and investigated. These included identification, projective identification, introjective identification and empathy. The identification process detailed ways a client communicates with the therapist through conscious and unconscious means. The therapist also receives information about the client via her own thoughts and emotional responses - classified as countertransference. Countertransferential responses via the introjective identification process, gives the therapist access to experiences that the client is, as yet, unable to put into words. The therapist then makes sense of her responses within the therapeutic relationship with the client. This dissertation also explores the benefits and cautions of the therapist utilising countertransferential responses.
Keywords: Countertransference; Psychology; Psychotherapy